Temporal fusion of entangled resource states from a quantum emitter - Yijian Meng; Carlos F. D. Faurby; Ming Lai Chan; Rasmus B. Nielsen; Patrik I. Sund; Zhe Liu; Ying Wang; Nikolai Bart; Andreas D. Wieck; Arne Ludwig; Leonardo Midolo; Anders S. Sørensen; et al. (Nature Communications)
Abstract Fusion-based photonic quantum computing architectures rely on two primitives: i) near-deterministic generation and control of constant-size entangled states and ii) probabilistic entangling measurements (photonic fusion gates) between entangled states. Here, we demonstrate these key functionalities by temporally fusing resource states deterministically generated using a solid-state spin-photon interface. Repetitive operation of the source leads to sequential entanglement generation, whereby curiously entanglement is created between the quantum states of the same spin at two different instances in time. Such temporal multiplexing of photonic entanglement provides a resource-efficient route to scaling many-body entangled systems with photons.